АСЦИТТІ КАРЦИНОМДЫ ЭРЛИХ ЖАСУШАЛАРЫНДАҒЫ ЭКЗОЦИТОЗДЫ ЗЕРТТЕУДІҢ ƏДІСТЕМЕЛІК ТƏСІЛДЕРІ (Experimental biology, 2015)
In the paper, the new method of the registration approach of the exocytosis process in Ehrlich ascitic carcinomatous cancer cells is shown by means of calcium signalization inductor.
Keywords: calcium signalization inductor